Analyzing the Effect of Variation in Shielding Gas Flow Rate and V Groove Type Towards Tensile and Metallographic Testing of GMAW Weld Joint of ASTM A53 and A36 - Herman Pratikno; Andrea Novia Samiyono; Wimala Lalitya Dhanistha (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2020)
Steel is a metal that commonly used in fabrication, engineering, and reparation activities in the structure construction industry. ASTM A53 steel is a low carbon steel with 0.25% to 0.3% of carbon content so it has a high weldability. ASTM A36 steel is a low carbon steel with carbon content of 0.25% to 0.29% and is often used in the floating building industry. This study aims to determine the effect of shielding gas flow rate and V-groove type to the tensile strength of A53 steel welded with A36 steel by Gas Metal Arc Welding (GMAW) method. The shielding gas level used is 100% CO2 with flow rate variations, including 15 liters/minute, 20 liters/minute, and 25 liters/minute. The groove types used are Single V-Groove and Double V-Groove. Tensile strength test result showed that in the welding process in this study, specimen with 25 liters/minute flow rate on the Double V-Groove had the highest tensile strength value of 516.73 MPa, with the narrowest HAZ width of 0,87 mm on A36’s HAZ and 1,22 mm on A53’s HAZ, and the smallest percentage of ferrite in the microstructure as much as 56.34% and 43.66% pearlite.